2018
DOI: 10.1017/ice.2018.321
|View full text |Cite
|
Sign up to set email alerts
|

Point-prevalence study of antimicrobial use in public hospitals in southern Sri Lanka identifies opportunities for improving prescribing practices

Abstract: A point-prevalence study of antimicrobial use among inpatients at 5 public hospitals in Sri Lanka revealed that 54.6% were receiving antimicrobials: 43.1% in medical wards, 68.0% in surgical wards, and 97.6% in intensive care wards. Amoxicillin-clavulanate was most commonly used for major indications. Among patients receiving antimicrobials, 31.0% received potentially inappropriate therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 6 publications
(12 reference statements)
3
13
1
Order By: Relevance
“…Conversely, a majority of patients with respiratory illnesses received an antibiotic prescription. These findings parallel previous observations in the inpatient setting in Sri Lanka, where lower respiratory tract infections were the most common indication for antibiotic therapy among hospitalized patients, as well as data from high-income countries showing high rates of outpatient antibiotic prescription for acute respiratory conditions [ 7 , 10 , 15 ]. Interventions targeting prescribing practices for acute respiratory tract infections thus represent a high-yield opportunity for antimicrobial stewardship.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, a majority of patients with respiratory illnesses received an antibiotic prescription. These findings parallel previous observations in the inpatient setting in Sri Lanka, where lower respiratory tract infections were the most common indication for antibiotic therapy among hospitalized patients, as well as data from high-income countries showing high rates of outpatient antibiotic prescription for acute respiratory conditions [ 7 , 10 , 15 ]. Interventions targeting prescribing practices for acute respiratory tract infections thus represent a high-yield opportunity for antimicrobial stewardship.…”
Section: Discussionsupporting
confidence: 89%
“…Decades of widespread antibiotic use have created selective pressure for the development of AMR, with increasing antibiotic consumption especially pronounced in LMICs [ 6 ]. A recent point-prevalence survey of antimicrobial use in Sri Lankan public hospitals revealed that more than one-half of all inpatients and nearly all patients in intensive care wards were receiving antimicrobials at the time of survey; approximately one-third of antimicrobials were deemed to be potentially inappropriate [ 7 ]. Systematic data on outpatient antimicrobial prescribing practices in Sri Lanka, however, remain limited.…”
Section: Introductionmentioning
confidence: 99%
“…In our study 103(48.1%) patients were on antibiotics. In a study done in Northern Ireland 44.1% of patients were given antibiotics 9 and in a study done in Sri Lanka 54.7% of patients were given antibiotics 10 . These studies had overall rates of prescription of antibiotics at similar levels to our study.…”
Section: Discussionmentioning
confidence: 98%
“…Tianchen et al, in a study done in Sri Lanka, found that the most commonly prescribed antimicrobial was amoxicillin/clavulanic acid. However, treating the patients with β-lactam-β-lactam inhibitor combination is recommended for a few conditions, for example, community-acquired pneumonia 10 . Therefore, adherence to the national and international guidelines should be emphasized in this circumstance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation